PROFESIONALITAS GURU BAHASA INDONESIA (DI PALEMBANG) DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Iryanti, Dian Kardina; Trisnawati, Trisnawati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Teachers play an important role in educators with the main task of educating, teaching, guiding, directing, training, evaluating, and evaluating students in early childhood education in the path of formal education, basic education, and secondary education. The problem in this research is to see how the Indonesian language teacher's professionalism towards learning literature in NU Middle School and Palembang State Middle School 16. The purpose of this study was to describe or explain the professionalism of Indonesian language teachers in Palembang NU Middle School and Palembang N 16 Middle School in the face of the era of the Industrial Revolution 4.0. The research method used is a qualitative descriptive method. The current condition of Indonesian Language teachers in Indonesia has begun to improve its quality. Learning languages in the process has indeed gone so well, but this fact is contrary to the conditions of learning Indonesian Literature in Middle School. Literary learning is often overlooked even as if it is totally untouched by the teacher. In the world of industrial revolution 4.0 education, the teacher is demanded for experts and equipped with the ability to understand the world of technology, because the world of industrial revolution 4.0 teachers must be experts in applying learning media, methods, techniques learning well, and equipped with knowledge that is expert in their respective fields.